Lo specchio rotto del Liebeskonzil: un caso di blasfemia nell’Impero guglielmino (Stato, Chiese e pluralismo confessionale, 2021)
SOMMARIO: 1. Panizza, un suddito infedele - 2. Scalpori e processi - 3. La pietra dello scandalo - 4. Un “teologo [...] eretico pittore di immagini sacre” - 5. Una scelta [quasi] obbligata - 6. Una foresta di simboli performativi - 7. Ordine religioso e ordine politico: l’ecosistema del processo - 8. Un “martire” a processo - 9. Martedì 30 aprile 1895, ore 19: la condanna - 10. Panizza sulla censura - 11. Morale religiosa come morale sessuale - 12. Manicomio, prigione, fuga - 13. “Un uomo fuori dal mondo”: ontologia di un blasfemo - 14. Istituzioni che succhiano il sangue.The broken mirror of Liebeskonzil: a case of blasphemy in the Wilhelminian EmpireABSTRACT: In 1895, due to the publication of the play Liebeskonzil, the writer Oskar Panizza was sentenced to one year imprisonment for blasphemy. Starting with such exemplary conviction, the essay reconstructs some aspects of the writer's existential and creative path, treating his vitriolic satires of religion as an access key to the political and social situation during the Wilhelminian Empire, where press laws and targeted use of crimes such as lèse majesté, obscenity and profanity, highlight the tenacity of Government, right-wing parties and Catholic Centre Party in pursuing the common purpose of silencing the opponents of the status quo.